Exocyclic DNA adducts as biomarkers for oxidative stress, dietary risk factors and cancer chemopreventive approaches - Bartsch, Helmut; Nair, Jagadeesan (Carcinogenic and anticarcinogenic factors in food, 2000)
This chapter contains sections titled: Exocyclic DNA Adducts as Biomarkers for Oxidative Stress, Dietary Risk Factors and Cancer Chemopreventive Approaches Abstract Introduction Results and discussion Increased exocyclic adduct formation as a consequence of LPO Etheno adducts Malondialdehyde-dG and propano-dG adducts Perspectives Biological Markers in Chemoprevention Research Abstract Introduction Validation studies Inter- and intra-individual variation Transitional studies: Nutritional and genetic factors and DNA damage PAH-DNA as a marker of lung cancer risk Nutritional status and lung cancer risk Genetic susceptibility to carcinogen exposure Early vs intermediate markers Modulation of biomarkers in an antioxidant vitamin trial in smokers Conclusions
Gesehen am 28.01.2021